Critical Points for the Production of Polymeric Microspheres Used in X-Ray Surgery - T. A. Bitkina; A. V. Basevich; V. M. Rodin (Разработка и регистрация лекарственных средств, 2020)
Introduction. Saturated polymer microspheres represent one of the leading developments in the field of chemoembolization. Due to the complicated multi-stage production in the Russian market, mainly foreign manufacturers of these products are represented, which may indicate the relevance of studying this topic.Aim. The aim of the work was to develop a technological scheme for the production of polymer microspheres and a description of critical control points of production.Materials and methods. The study of the intermediate product was carried out using a Levenhuk D320L microscope (Levenhuk Inc, USA). Analysis of production control points was carried out by the HACCP (Hazard analysis and critical control points) method.Results and discussion. As a result of the study, the main technological stages of the production of microspheres, which are a copolymer of vinyl alcohol and sodium acrylate, have been identified and described. For each technological stage, control critical points are determined with an indication of the controlled parameters and control methods. The photographs of the intermediate product at intermediate stages are shown.Conclusion. A technological scheme for the production of microspheres has been developed. The analysis of critical control points of the stages of the main production process is carried out. Identified irreversible critical points of production.